Ethylamines as Corrosion Inhibitors for Zinc in Nitric Acid - Vashi, R.T.; Desai, S.A.; Desai, P.S. (Asian Journal of Chemistry, 2010)
The corrosion of zinc in nitric acid containing ethylamines has been studied. In plain nitric acid, the corrosion rate increases with the acid concentration and temperature. At constant acid concentration, the inhibition efficiency of ethylamines increase with the inhibitor concentration. Similarly, at constant inhibitor concentration, the inhibition efficiency increases with the increase in concentration of acid. At 40 mM inhibitor concentration in 0.01 M HNO3 at 301 ±1 K for 24 h immersion period, the inhibition efficiency of inhibitors decreases in the order:ethylamine (92 %) > diethylamine (91 %) > triethylamine (82 %). As temperature increases, the value of ΔGa increase while percentage of inhibition decrease. Plot of log (θ/1-θ) vs. log C results in a straight line suggest that the inhibitors cover both anodic and cathodic regions through general adsorption following Langmuir isotherm. Anodic and cathodic galvenostatic polarization curves show little anodic but significant cathodic polarization.